Become a franchise owner! : - Libava, Joel (Wiley, 2012)
With more and more professionals looking for alternatives totraditional corporate employment, Become a Franchise Owner!informs would-be franchise owners of the joys and perils ofpurchasing a franchise. Authored by a trusted, feisty,tell-it-how-it-is independent franchise industry insider, this bookoffers straightforward, step-by-step tips and advice on how toproperly (and carefully) research and select a franchise business.